Modéliser les pratiques pastorales d’altitude dans la longue durée - Mélanie Le Couédic (Cybergeo)
The Pyrenean mountain pastures are most often a community resource, exploited by communities of people in high valleys. Large-scaled, territorial divisions of these mountain summer pastures are essentially defined by the practice during the pasture-ground livestock from pastoral huts. To consider these practices and shares at different times, from the pastoral sites documented by archaeology, the archaeological study aims to understand the physical and social determinants of livestock routes, and their material correlates.A lot of thought was given on the organization of data used to work on the dynamics of pastoral land in the long term in Bearn. A conceptual data model was designed according to the HBDS method based on hypergraphs; it involves the explaining of all phenomena that come into play and allows the integration of different spatial and temporal scales. Interactions between men, resources and herds are planned over an extended period, at different levels of spatiotemporal organization, from the work of geo-agronomists, the knowledge of landscape ecology and archaeology. Used as an integrator tool, this model has been constructed in a dialectical process between data acquisition and their structuring. The formalization and modelling are an effective way to understand a complex system enlightened by several sources at multiple scales of space and time.